2016
DOI: 10.1371/journal.pone.0150708
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Spatial Updating with Reduced Visual Information

Abstract: PurposeSpatial updating refers to the ability to keep track of position and orientation while moving through an environment. People with impaired vision may be less accurate in spatial updating with adverse consequences for indoor navigation. In this study, we asked how artificial restrictions on visual acuity and field size affect spatial updating, and also judgments of the size of rooms.MethodsNormally sighted young adults were tested with artificial restriction of acuity in Mild Blur (Snellen 20/135) and Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…The good performance of these subjects is consistent with previous findings that artificial blur (in the range 20/500–20/800) had little impact on the perceived distance of visible objects for normally sighted subjects. 21,22 But in our previous study, 13 we found that normally sighted subjects with severe blur (logMAR 1.65), but not mild blur (logMAR 0.83), exhibited larger errors in room-size judgments. Only two of our low-vision subjects had acuities similar to or worse than the “severe blur”—LV05 (logMAR 1.62) and LV17 (logMAR 1.96).…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…The good performance of these subjects is consistent with previous findings that artificial blur (in the range 20/500–20/800) had little impact on the perceived distance of visible objects for normally sighted subjects. 21,22 But in our previous study, 13 we found that normally sighted subjects with severe blur (logMAR 1.65), but not mild blur (logMAR 0.83), exhibited larger errors in room-size judgments. Only two of our low-vision subjects had acuities similar to or worse than the “severe blur”—LV05 (logMAR 1.62) and LV17 (logMAR 1.96).…”
Section: Discussionmentioning
confidence: 58%
“…36,37 Our previous study included conditions in which normally sighted subjects were pushed in a wheelchair along the three-segment paths to determine if reduced proprioceptive input would result in poorer spatial updating. 13 The wheelchair subjects did not exhibit poorer updating performance than the walking subjects, nor did they show greater dependence on visual condition. These results confirm that vestibular cues can be effective for spatial updating.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations